Exploration of educational building with cultural elements using shape grammar - Sebastian, Heng Junjie (2013)
Shape grammars are used for developing computational algorithms in production systems that generate geometric shapes. Existing researches on shape grammars in applications focus on product design, pattern generation, residential building design and architectural design. However, research on the educational building design with different aspects in functions and environments are not much addressed. This research explores the application of shape grammars in generating educational building designs with cultural, functional and artistic issues. Basic building blocks for Western, Chinese, European and Malay culture are developed to construct the educational buildings. Existing building blocks like L-shapes oriented with specific angles could be combined to form a new building concept. This new concept can uniquely represent a particular educational building characteristic. During the design process, other rules are activated to embed new shapes within the basic building block. The rules are executed to generate designs to provide students a spacious environment for study and related activities. Other concepts like pure, rational and energy saving are also expressed by the rules. The system takes into account of different requirements like costs, functions, space, culture, environment, the number of classrooms, public halls, windows and doors. For example, the urban areas in Kuala Lumpur consist of many high rise buildings, like office buildings, residential apartments and others. Under these constraints, a stylistic educational building with high scores can be generated by the system as it suits this particular set of requirements. In future, more on-site applications and surveys will be conducted to verify the advantages in using the system to explore educational building designs. Other enhancements would be the automation of the formulation and execution of the shape grammar rules by integrating artificial intelligence techniques such as fuzzy logic, neural network and genetic programming.